2022
DOI: 10.3390/bios12070530
|View full text |Cite
|
Sign up to set email alerts
|

Probing Denaturation of Protein A via Surface-Enhanced Infrared Absorption Spectroscopy

Abstract: We apply surface-enhanced infrared absorption (SEIRA) spectroscopy to monitor the denaturation process of a surface-bound protein A monolayer. Our proposed platform relies on a plasmonic metasurface comprising different spatial subregions (“pixels”) that are engineered to exhibit different resonances covering the infrared region of the electromagnetic spectrum that is matched to the vibrational modes of the Amide groups. Specifically, we are able to determine changes in the Amide I and Amide II vibration coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Further, Gao et al [69] have developed a generalized classical model of SEIRA spectroscopy that shows that mid-IR surface plasmon resonances can be used for detection of vibrational bands. SEIRA spectroscopy has also been incorporated to monitor protein denaturation in the infrared regime using engineered plasmonic metasurfaces [70]. In a latest report by Najem et al [71] enhanced infrared sensing is demonstrated using aluminium nanostructured bowties on a metal-insulator-metal (MIM) platform.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Gao et al [69] have developed a generalized classical model of SEIRA spectroscopy that shows that mid-IR surface plasmon resonances can be used for detection of vibrational bands. SEIRA spectroscopy has also been incorporated to monitor protein denaturation in the infrared regime using engineered plasmonic metasurfaces [70]. In a latest report by Najem et al [71] enhanced infrared sensing is demonstrated using aluminium nanostructured bowties on a metal-insulator-metal (MIM) platform.…”
Section: Introductionmentioning
confidence: 99%